1978
DOI: 10.1017/s0014479700008498
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil-applied Micronutrients on Cassava (Manihot esculenta) in Malaysian Tropical Oligotrophic Peat

Abstract: SUMMARYTwo experiments to investigate the micronutrient requirements of cassava (cv Black Twig) on Malaysian peat soil are described. Cu was found to be the only essential micronutrient and Mn, Zn, Fe, Mo and B were not needed. Fertilizing with 20 kg/ha of copper sulphate approximately tripled tuber dry matter, and starch and Cu uptake, but applying 10 kg/ha of copper sulphate gave the same results. Each crop of cassava absorbed only about 2% of the applied Cu, giving a leaf Cu content of about 14 ppm compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…For example, basipetal auxin transport appeared in profile 11 (upregulated pattern), whereas response to auxin stimulus was found in profile 4 (downregulated pattern). Interestingly, metal ion transport and copper ion transport were also highlighted in profile 11, which is highly consistent with the physiological requirement of cassava for copper (Chew et al 1978). Furthermore, defense response, response to abiotic stimulus, and response to wounding were also noticeable, possibly due to stress responses that occurred during sample collection.…”
Section: Discussionsupporting
confidence: 69%
“…For example, basipetal auxin transport appeared in profile 11 (upregulated pattern), whereas response to auxin stimulus was found in profile 4 (downregulated pattern). Interestingly, metal ion transport and copper ion transport were also highlighted in profile 11, which is highly consistent with the physiological requirement of cassava for copper (Chew et al 1978). Furthermore, defense response, response to abiotic stimulus, and response to wounding were also noticeable, possibly due to stress responses that occurred during sample collection.…”
Section: Discussionsupporting
confidence: 69%
“…To the opposite, while Zn and Cu content in the soil declined, soil Mn and Fe content significantly improved with the application of mineral fertilizer, mainly at 8 and 12 MAP. A research from Malesia revealed that Cu was found to be the most limiting micronutrient for cassava production (Chew et al 2008). In this research, the Cu released to the soil was statistically not significant following manure application-where we expect Cu release to the soil, while it was significantly reduced for the soils treated by NPK fertilizer-where we did not applied Cu.…”
Section: Discussionmentioning
confidence: 49%
“…Apart from occasional culture of air-cured Javanese tobacco, peat has not been used for tobacco, mainly because of possible adverse effects of its high N content (1.5-2.5% of peat dry matter) on leaf quality (De Geus, 1974). However, the recent finding that peat N is mostly unavailable, and that liming releases only small amounts that are usually insufficient to meet crop needs (Chew et al, 1976), indicates that the N status of tobacco grown on peat can be controlled by the amount of N added as fertilizer, thus enhancing the tobacco potential on this largely unexploited soil of which there are 0.8m ha. Preliminary field tests in 1975 confirmed this, with yields of about 640 kg/ha of dry Javanese tobacco leaf and 400-1750 kg/ha of good-quality flue-cured tobacco (cv NC95), though the latter varied in yield according to soil pH, with stunting and yellowing at low lime status (pH<3.9).…”
mentioning
confidence: 99%